(untitled) (Konturen, 2022)
This article explores anti-racist, feminist performance and video art by kate-hers RHEE and Patty Chang. Parodic performances of awkward sexual encounters in works such as RHEE’s The Chocolate Kiss (2013) and Chang’s The Product Love (2009) embody and deconstruct identity formation within transnational German and Asian American contexts. I explore how RHEE and Chang distinctly challenge sexist and racist stereotypes and the objectification of Asian women, while problematizing cultural categorization through (mis)translations and poetic relations. The article illuminates how these artists complicate Asian American identities via variegated explorations of critical race theories and connected histories of cross-cultural representation.